Geographical Characterization of Çekiste Olive Oils from Southwest of Turkey with QTOF-MS - Uckun , Ayca Akca (Emerging Challenges in Agriculture and Food Science Vol. 5, 2022)
The goal of this research is to determine the impact of Cekiste olive oils in various areas and to demonstrate variances in geographic locations while using the geographical indicator label. The impacts of geographical locations on the chemical characteristics of the Cekiste olive oil variety planted in six distinct places (Birgi, Bademli, Beyazit, Yenicekoy, Zeytinlik, Uzumlu) were investigated. GIS was used to construct each location's agricultural ecological map. Fatty acid, sterol, and phenolic analysis were performed on olive oil samples. Furthermore, the geographical fingerprints of olive oil samples from various regions were determined using the LC IMS Qtof spectrometer and Progenesis QI software. The results revealed that the oil quality of some places varied significantly (p <0.05) depending on the olive producing area, while others do not. The Principal Component Analysis of the many sites investigated found that the "geographical location" factor has a substantial impact on the quality of olive oil.